A MODEL OF CLEAN WATER SUPPLY AND IMPROVEMENT OF ENVIROMENTAL SANITARY CONDITION AT RESIDENTIAL CLUSTER IN MEKONG DELTA, VIETNAM - Lan Chi, Nguyen Thuy (GeoScience Engineering, 2016)
In accordance with Decision 99/TTg dated 9/2/1996 and Decision 173/TTg dated 6/11/2001 of the Prime Minister regarding to construction program of residential cluster (residential floodfree areas), these residential areas as constructed would be fully equipped with critical infrastructures and services such as water supply and drainage works, toilets with sanitary appropriateness, etc. to ensure the environmental sanitary conditions at these residential cluster. However, the actual surveys done at these residential cluster in Mekong delta show that many arising problems must be addressed to enable the local communities to have better living conditions and ensure the sanitary conditions and environmental safety.